Psychological impact of cancer diagnosis among gynaecological cancer subjects in a tertiary care centre - Nanjaiah, Ranjini; Khan, Mudassir A.; Rao, Vadiraja N. (International Journal Of Community Medicine And Public Health, 2017)
Background: The survival rate of cancer patients has improved and focus has shifted to improve the quality of life of the survivors. An adequate knowledge is required for psychosocial interventions and designing programs aimed at improving the quality of life of the cancer patients. The purpose of the study is to assess Anxiety and Depression [Psychiatric morbidity] among gynaecological cancer subjects and its association with duration since diagnosis, type of cancer, mode of treatment and socio-demographic variables. Methods: This is an interview based cross sectional study involving 131 patients diagnosed to have gynaecological cancer who were evaluated using hospital anxiety and depression scale (HADS). The gynaecological and socio-demographic data was analyzed for any correlation with HADS scores. Results: The prevalence of at least one psychiatric disorder was 90% (n=118). Sixty subjects [45.8%] had anxiety, 71 subjects [54%] had depression and 118 cases [90%] had psychiatric morbidity. Patients suffering for less than three months had anxiety; three to 12 months were both anxious and depressed; more than 12 months were depressed. Young women with less education were more anxious compared to educated women. Conclusions: Given a gynaecological cancer an individual will have 0.9 chance of developing psychiatric morbidity. Young women with less education aware of cancer diagnosis for three to 12 months were at increased risk and needs intervention. As cancer incidence is increasing and psychiatric morbidity is common among cancer patients, training of health care personnel in cancer screening and recognizing patients with common mental disorders is required to improve their quality of life. Creating awareness of public regarding risk factors of cancers, importance of screening and cancer treatment is necessary.